WAYS TO FROM INTEREST IN SPORTS AMONG TEACHERS THROUGH PHYSICAL EDUCATION LESSONS (Web of Teachers: Inderscience Research, 2024)
This article includes information on the development of physical and psychological qualities of the physical culture teacher on the basis of pedagogical professional competence and skills, creative approach, psychophysiological coexistence of the child on the basis of age periods, the use of psychotraumatic signs during the lesson.